2004
DOI: 10.1021/jm0303711
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and Antimalarial Efficacy and Safety of Artemisinin-Derived Trioxane Dimers in Rodents

Abstract: In only four chemical steps from naturally occurring artemisinin (1), trioxane dimers 6 and 7 were prepared on a multigram scale in overall 32-44% yields. In mice, both isonicotinate N-oxide dimer 6 and isobutyric acid dimer 7 were considerably more antimalarially efficacious than clinically used sodium artesunate (2) via both oral and intravenous administration. In the transgenic adenocarcinoma of mouse prostate model, some of the trioxane dimers had potent anticancer activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 13 publications
1
103
0
Order By: Relevance
“…* To whom correspondence should be addressed. tives) [1][2][3] . However, the traditional trial-and-error methods used to identify active compounds from numerous herbal compounds in TCM are time-consuming and labor intensive.…”
Section: Introductionmentioning
confidence: 99%
“…* To whom correspondence should be addressed. tives) [1][2][3] . However, the traditional trial-and-error methods used to identify active compounds from numerous herbal compounds in TCM are time-consuming and labor intensive.…”
Section: Introductionmentioning
confidence: 99%
“…14 The observation that ART inhibits the growth of many transformed cell lines has led to the hypothesis that the drug can also be useful for the treatment of human neoplasia. [15][16][17][18][19][20][21][22][23][24] As shown by us and others, [25][26][27][28][29][30][31][32] ARSs reveal antiangiogenic features in vitro and in vivo. The molecular determinants of the antiangiogenic activity of ARSs are incompletely understood at present.…”
Section: Introductionmentioning
confidence: 99%
“…Dihydroartemisinin peaked in the blood (0.7 μg/mL) at 12 h, and decreased to 0.18 μg/mL at 24 h. After 24 h, artemisinin concentration in feces was 2.4 μg/g, indicating artemisinin's poor bioavailability in goats when provided orally and as capsules. Posner et al (2004) observed high time-dependent first-pass metabolism in the gut and liver, this drug are conjugates such as glucuronides and can be eliminated through phase-II metabolism. Therefore, artemisinin has low water solubility, resulting in poor and erratic absorption upon oral administration, so the artemisinin conjugation reactions and hydrolysis are the principal reasons these derivatives have a short half-life.…”
Section: Discussionmentioning
confidence: 99%